SPORT AS A SOCIAL AND POLITICAL OBSERVATORY (Jóvenes en la Ciencia, 2015)
The purpose of this research is to understand the underlying historical and political factors which have affected the inclusion of women in international sports. It is maintained that gender inequality still exists in many major sporting competitions. As such, it is necessary to assess what has been done before and what still needs to be done in order to combat gender inequality on the field and outside of it. We will look at how sports is used as a civilizing method to uphold the patriarchy. We will also discuss how feminist movements have influenced the advancement of women’s rights in sports. Then, the Olympic Games, FIFA, and the media are scrutinized for their history of inclusion and empowering women. This will allow for a multi-faceted study of sexism in global sports as we move towards full, indiscriminate participation of female athletes in global competitions.